2013
DOI: 10.1007/s00701-013-1821-y
|View full text |Cite
|
Sign up to set email alerts
|

Surgery of recurrent brain metastases: retrospective analysis of 67 patients

Abstract: Surgery of recurrent brain metastasis is an important therapeutic option. A subgroup of patients, defined by prognostic factors, will profit with improvement of symptoms and prolongation of the overall survival time. Even long-term survivors can be expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 40 publications
5
14
1
Order By: Relevance
“…Moreover, the study should provide a basis upon which other local salvage treatment concepts, such as OTR, could be compared to. In a mere comparison of survival data, PRS rates after OTR are comparable to our PRS rates after salvage CyberKnife: retrospective data on salvage OTR suggest a PRS range between 7.5 and 12.9 months [4-5]. These ranges are determined by disease- and patient-specific differences.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, the study should provide a basis upon which other local salvage treatment concepts, such as OTR, could be compared to. In a mere comparison of survival data, PRS rates after OTR are comparable to our PRS rates after salvage CyberKnife: retrospective data on salvage OTR suggest a PRS range between 7.5 and 12.9 months [4-5]. These ranges are determined by disease- and patient-specific differences.…”
Section: Discussionsupporting
confidence: 71%
“…The major argument for surgery in this patient cohort may be seen in the clinical improvement which is, in line with the current literature, the strongest predictor for further survival after recurrent BM treatment [4,8,16].…”
Section: Discussionsupporting
confidence: 79%
“…However, the role of surgery for pretreated, recurrent BM is not yet de ned, and only scarce data, originating from the premolecular era, are available. Only a few studies have reported on the feasibility of (re-)surgery in patients with single or multiple recurrent BM [8,9,13,14]. They included narrowly de ned patient cohorts previously treated by either surgery [8,15] or sRS [14,16], and reported median survival rates after resection of between 7.5 and 11.5 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Median OS after upfront STI was 37.5 months for all 48 patients, 37.5 months for recurrences with pure or combined histology (n = 42), and 40.3 months for patients with pure radiation necrosis (n = 6) (p = 0.13). Median OS noted in previously published studies was much lower at 7.5 to 19 months (Table 4) [10,11,[17][18][19][20]. The longer median survival in our study can be attributed to the development of systemic therapy, improved care of cancer patients, and advances in surgical techniques.…”
Section: Discussionmentioning
confidence: 39%